COMPOSITION FOR VOICES: JEAN-LUC NANCY'S MUSICAL SUBJECT. - Lindberg, Susanna (Symposium: Canadian Journal of Continental Philosophy / Revue Canadienne de Philosophie Continentale)
This article presents Jean-Luc Nancy's ideas of music in relation to being singular plural. Nancy elaborates on the themes of sharing of voices and of resonance in several texts, and he relates resonance specifically to sound, voice, and music. Although in other contexts Nancy thinks that the question of the subject belongs to the past, he maintains the question of the subject in the context of sonority. We will see that this subject is not only the subject of sensation but more precisely the musical subject. Finally, we will see how musical themes help him deconstruct the idea of community on individual, dialogic, and collective levels. Nancy opposes his idea of musical community to the total musical community that characterizes Romanticism. In the end, he objects to all forms of formatting in genres and invites to open, active, and inventive forms of listening all sounds that resonate in the world.